Chronic Cough, Reflux, Postnasal Drip Syndrome, and the Otolaryngologist. (10th April 2012) - Sylvester, Deborah C.; Karkos, Petros D.; Vaughan, Casey; Johnston, James; Dwivedi, Raghav C.; Atkinson, Helen; Kortequee, Shah
Abstract : Objectives . Chronic cough is a multifactorial symptom that requires multidisciplinary approach. Over the last years, general practitioners refer increasingly more chronic cough patients directly to the otolaryngologist. The aim of this paper is to highlight the issues in diagnosis and management of chronic cough patients from the otolaryngologist perspective. Design . Literature review. Results . Gastroesophageal reflux and postnasal drip syndrome remain one of the most common causes of chronic cough. Better diagnostic modalities, noninvasive tests, and high technology radiological and endoscopic innovations have made diagnosis of these difficult-to-treat patients relatively easier. Multidisciplinary assessment has also meant that at least some of these cases can be dealt with confidently in one stop clinics. Conclusions . As the number of referrals of chronic cough patients to an Ear Nose Throat Clinic increases, the otolaryngologist plays a pivotal role in managing these difficult cases.